Outcome of buccal mucosal patch graft in the Management of recurrent hypospadias urethrocutaneous fistula - Jasim, Ahmed kh. (Journal of the Faculty of Medicine Baghdad, 2015)
Background: urethrocutaneous fistula after hypospadias surgery repair is the most common complication and remains a frustrating problem for surgeon and the patient. The problem is exacerbated because the urethrocutaneous fistula may recur which adds more demands surgery.Objectives: The purpose of this study is to evaluate of the use of oral mucosal graft for management of recurrent urethrocutaneous fistula after hypospadias repair.Patients and Methods: twelfth patients with age ranging from 4 year to 15 years were presented with history of recurrent fistula. Most of fistula were located in proximal penile and penoscrotal region (58.3%) . those patients were repaired by using oral mucosal graft with mean postoperative follow up period up to 6 months.Results: analysis of results showed 10 out of 12 cases (83.3%) had a final successful outcome with no recurrent fistula during follow up period. The two patients with failed repair were candidate for another attempt for fistula repair later on. No donor site morbidity was observed in all patients.Conclusion: Oral mucosal graft showed very good take and promising results when used for management of recurrent urethrocutaneous fistula after hypospadias repair.